Transformasi Supervisi Pendidikan Islam: Dari Paradigma Otoriter Menuju Kolaboratif-Humanis - Ariyanto Ariyanto; Meti Fatimah (Lembaga Yasin AlSys, 2026)
Islamic education supervision plays a strategic role in improving educational quality through the professional development of teachers. However, supervision practices in various Islamic educational institutions remain largely influenced by a traditional paradigm that is authoritarian, inspection-oriented, administrative, and focused on fault-finding. This condition reduces the effectiveness of supervision in strengthening teacher professionalism and may generate resistance, weaken motivation, and limit teachers’ creativity. In addition, a gap remains between the modern concept of humanistic and collaborative supervision and its implementation in educational practice. This study aims to examine the transformation of the Islamic education supervision paradigm toward a collaborative-humanistic supervision model and to analyze the integration of Islamic values in its implementation. This study uses a library research method with a descriptive qualitative approach through a review of books and scholarly articles related to Islamic education supervision. The findings indicate that Islamic education supervision has shifted from a control-based approach toward a professional development model that is more humanistic, democratic, participatory, and reflective. The collaborative-humanistic approach is considered relevant to contemporary Islamic education because it positions teachers as professional partners rather than objects of inspection. Clinical supervision also emerges as an effective model for improving learning quality through dialogical and reflective processes. The integration of the values of amanah, ihsan, musyawarah, and islah strengthens the distinctive character of Islamic education supervision by ensuring that supervision is not only directed toward competence improvement but also toward teachers’ moral and spiritual development. This study contributes theoretically to the development of Islamic education supervision literature and provides practical implications for supervisors, school leaders, and Islamic educational institutions in implementing supervision that is collaborative, humanistic, reflective, and grounded in Islamic values.